The Influence of Leadership Style and Organizational Culture on Employee Performance Through Motivation as Mediation (At PT. Siam-Indo Gypsum Industry) - Bhakti Yuliadi Rahmatullah; Kasmir Kasmir (Dinasti Publisher, 2023)
The goal of this research is to look at the impact of Leadership Style and Organizational Culture on Employee Performance using Motivation as a mediation. With a random sample approach of 176 people, the population of this study is all employees of PT. Siam-Indo Gypsum Industry in Bekasi Regency. The Structural Equation Model-Partial Least Squares is used to analyze the data (SEM-PLS). According to the findings of this study, Leadership Style and Organizational Culture have a direct and considerable beneficial influence on motivation. Employee performance is directly affected by motivation in a favorable and meaningful way. Leadership Style and Organizational Culture have no direct influence on employee performance, but they do have a considerable effect with perfect mediation through Motivation. The article discusses the ramifications of this discovery. It is recommended that leaders be able to cooperate well with their subordinates, provide clear and easy-to-understand work procedures, and provide awards and work according to their abilities.